A quantitative analysis of joint phasing and efficiency in the Olympic clean - Byers, J.; Wu, T.; Gervais, P. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
For an athlete to be successful in the classical lifts, the clean and jerk and the snatch, he or she must display excellent coordination between body segments in a powerful fashion (Jones, 1991). These characteristics make Olympic style weightlifting highly beneficial and transferable to other sports (Caravan et al, 1996). It is widely accepted that to produce the maximum force, all three of the hip, knee and ankle joints must be fully extended (Martyanov, 1988). It is theorized that the premature extension of the trunk, in relation to the knees, will lead to excessive horizontal bar movement and subsequent loss of force, or failure to lift. The purpose of this study was to examine joint phasing for efficiency during the Olympic power clean. The results would be important for the development of future coaching protocol to aid in the continuing improvement of the technical mastery of the Olympic style lifts across all applications.